2019
DOI: 10.1371/journal.pone.0216047
|View full text |Cite|
|
Sign up to set email alerts
|

Fatty acid profile, physicochemical composition and sensorial attributes of salted and sun-dried meat from young Nellore bulls supplemented with condensed tannins

Abstract: The objective of this study was to evaluate the effect of condensed tannin inclusion (0, 10, 30 or 50 g/kg of dry matter (DM) total) from Acacia mearnsii extract on the fatty acid profile, physicochemical quality and sensorial analysis of salted and sun-dried meat from young Nellore bulls. The inclusion of condensed tannin extract in the young bulls’ diets promoted a quadratic reduction in the lipid content. There was a linear increase in the water retention capacity, cooking weight loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…Promotion or inhibition of the BH of certain cis 18:1 isomers with tannins has also been described (e.g., cis-9, -11 and -13 18:1; Khiaosa-ard et al, 2009; Buccioni et al, 2017a) and subsequently confirmed in milk (e.g., Pascual et al, 2019) and meat Gesteira et al, 2019;. In the case of the oleic acid, SCD activity would act as a confounding factor when examining the effects of tannins on meat and milk Bernard et al, 2013).…”
Section: Effects On Intermediates Of Ruminal Fatty Acid Metabolismmentioning
confidence: 92%
See 1 more Smart Citation
“…Promotion or inhibition of the BH of certain cis 18:1 isomers with tannins has also been described (e.g., cis-9, -11 and -13 18:1; Khiaosa-ard et al, 2009; Buccioni et al, 2017a) and subsequently confirmed in milk (e.g., Pascual et al, 2019) and meat Gesteira et al, 2019;. In the case of the oleic acid, SCD activity would act as a confounding factor when examining the effects of tannins on meat and milk Bernard et al, 2013).…”
Section: Effects On Intermediates Of Ruminal Fatty Acid Metabolismmentioning
confidence: 92%
“…Furthermore, many of these intramuscular FA profiles were not comprehensive enough to study even the most relevant FA. Indeed, it is of note that trans-11 18:1 is not reported in several studies Gesteira et al, 2019). Overlooked coelutions between trans-11 18:1 and other 18:1 isomers (in particular trans-10 18:1) may also exist, which obliges to be cautious in the interpretation of poorly detailed FA profiles.…”
Section: Effects On Intermediates Of Ruminal Fatty Acid Metabolismmentioning
confidence: 96%
“…According to this result, Lobón, et al [28] suggested that the use of quebracho to improve biohydrogenation should be wisely excluded. In addition, Acacia mearnsii extract was investigated in serial doses at 10, 30 and 50 g/kg DM in total mixed rations (TMRs), forage and concentrate (40:60), and the concentrations of PUFA in meat were observed [50]. The desaturase index was reported to be increased after supplementation with dietary tannins, but the amount of CLAs was decreased.…”
Section: The Effects Of Dietary Tannins On De Novo Synthesis and Endogenous Desaturationmentioning
confidence: 99%
“…However, the effect of mimosa CT extract on oxidation of myoglobin in meat was contradictory: one of these works reported the reduction of metmyoglobin formation [90], while the other showed that supplementation of diets with mimosa CT extract did not affect the myoglobin oxidation [91]. Lipid oxidation in salted and sun-dried meat from bulls fed an oil-supplemented (42.5 g/kg DM of soybean oil) diet composed of 40:60 forage and concentrate was also not affected by increasing levels of mimosa extract in the diets (10, 30 and 50 g/kg DM) [92]. Similar results were also found by Staerfl et al [93], who reported that supplementation of maize silage with concentrate containing 141 g/kg of mimosa extract did not improved the oxidative stability of perirenal fat of bulls.…”
Section: Condensed Tannin Extractsmentioning
confidence: 98%